2008
DOI: 10.1177/1538574407306791
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Deep Venous Insufficiency Caused by Congenital Absence of the Infrarenal Inferior Vena Cava

Abstract: Congenital absence of the inferior vena cava (CAIVC) is a rare vascular defect, commonly reported as a fortuitous finding because patients are typically asymptomatic of the condition itself but are symptomatic of associated conditions such as congenital heart disease, polysplenia, asplenia, and inversion of bowel viscera. The presence of CAIVC is probably underestimated because CAIVC may not be detected by compression B-mode ultrasonography. By use of computed tomography, we diagnosed a case of CAIVC in a youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Giving the rarity of the disease, there is no evidence based approach management [ 14 ]. Treatment is directed towards prevention of thrombosis formation or recurrence; life-long vitamin K antagonist is required for patients with IVCA in addition to elastic stocking and leg elevation to relieve venous stasis [ 1 , 2 , 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving the rarity of the disease, there is no evidence based approach management [ 14 ]. Treatment is directed towards prevention of thrombosis formation or recurrence; life-long vitamin K antagonist is required for patients with IVCA in addition to elastic stocking and leg elevation to relieve venous stasis [ 1 , 2 , 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is directed towards prevention of thrombosis formation or recurrence; life-long vitamin K antagonist is required for patients with IVCA in addition to elastic stocking and leg elevation to relieve venous stasis [ 1 , 2 , 8 , 15 ]. Surgical correction can be an option for management depending on the severity of the venous stasis symptoms and response to medical and conservative treatment [ 11 , 14 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two most common presentations associated with IVC agenesis are thrombosis of deep veins in 76.2% of cases and edema in 23.8% of cases [5] . The first ever case of IVC reconstruction using polytetrafluoroethylene PTFE graft for symptomatic congenital absence of IVC was described in 2008 [1] . Early surgical treatment for IVC agenesis followed by need for oral anticoagulation afterwards has been suggested in the literature as it has been shown potentially reverse the debilitating venous insufficiency associated with it [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Congenital anomalies of the inferior vena cava (IVC) are infrequent and the incidence is reported to be 0.7–8.7% in general population. Congenital absence of IVC can either be isolated or associated with other anomalies [1] . In most cases of isolated asymptomatic congenital absence of IVC lifelong anticoagulation is indicated [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Since she had not developed a DVT yet, we felt that aspirin prophylaxis was appropriate at this time. Given that the patient's symptoms were reproduced only by intense activity and not present at rest, surgical management was appropriately delayed at this time; a case report on the surgical reconstruction of an absent infrarenal IVC showed that it was efficacious for symptom relief, but that it should be performed only with a high level of symptom severity, and that oral anticoagulation would be the preferred treatment for the majority of cases ( 14 ).…”
Section: Discussionmentioning
confidence: 99%